2009
DOI: 10.1016/j.heares.2009.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Primate auditory recognition memory performance varies with sound type

Abstract: Neural correlates of auditory processing, including for species-specific vocalizations that convey biological and ethological significance (e.g. social status, kinship, environment),have been identified in a wide variety of areas including the temporal and frontal cortices. However, few studies elucidate how non-human primates interact with these vocalization signals when they are challenged by tasks requiring auditory discrimination, recognition, and/or memory. The present study employs a delayed matching-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 75 publications
1
21
1
Order By: Relevance
“…A recent study of nonserial auditory DMS in rhesus monkeys by Ng et al (30) reported better performance and faster reaction times for conspecific vocalizations relative to other sound categories (similar to the categories used here) at delays of 5 s. In contrast, as shown in Fig. 3, our results indicate slightly better performance for tonal stimuli compared with all others, including monkey vocalizations.…”
Section: Effect Of Small Stimulus Setscontrasting
confidence: 55%
“…A recent study of nonserial auditory DMS in rhesus monkeys by Ng et al (30) reported better performance and faster reaction times for conspecific vocalizations relative to other sound categories (similar to the categories used here) at delays of 5 s. In contrast, as shown in Fig. 3, our results indicate slightly better performance for tonal stimuli compared with all others, including monkey vocalizations.…”
Section: Effect Of Small Stimulus Setscontrasting
confidence: 55%
“…Similarly, European starlings are capable of learning to recognize pitch-shifted conspecific songs, but not pitch-shifted piano melodies (Bregman et al, 2012). A mnemonic advantage for CVs has also been reported in two recent studies of auditory short-term memory in humans (Weiss et al, 2012) and non-human primates (Ng et al, 2009). …”
Section: Introduction: Ecological and Behavioral Significance Of Csupporting
confidence: 57%
“…However, these possibilities should be considered and tested when possible. On the plus side, there are several studies showing that different types of sounds in non-human primates elicit different behavioral and neural responses (Poremba et al, 2004; Ng et al, 2009), but future controlled testing of sounds with a similar frequency range to vocalizations and consideration of the amount of experience with the sounds will need further consideration. In addition, we must study whether the neural processes underlying associative conditioning also underlie learning of CVs and the relationship between conditioning, experience, and memory encoding.…”
Section: Summary and Future Research Directionsmentioning
confidence: 99%
“…Each sound stimulus, 220 to 500 ms (ms) long, was digitized and processed with a sampling frequency of 44,100 Hz and consisted of 8-bit monorecorded sound clips. A collection of 96 standard stimuli was used and classified into eight sound types similar in manner to Ng et al (2009). Animal vocalizations (n = 12) included sounds recorded from birds and domestic animals (e.g., cat and dog).…”
Section: Auditory Stimulimentioning
confidence: 99%
“…Each animal was trained on the DMS task with auditory stimuli as described in Ng et al (2009). The task employed go/no-go response rules for the auditory DMS task (Fig.…”
Section: Auditory Dms Taskmentioning
confidence: 99%